miR-582 Suppresses the Proliferation of B-Cell Precursor Acute Lymphoblastic Leukemia (BCP-ALL) Cells and Protects Them From Natural Killer Cell-Mediated Cytotoxicity - Li, Xinxin; Zhang, Yufei; He, Fei; Gao, Dan; Che, Bo; Cao, Xiuli; Huang, Siyong; Zheng, Minhua; Han, Hua (Frontiers in Immunology, 2022)
B-cell precursor acute lymphoblastic leukemia (BCP-ALL) is a malignancy characterized by the aberrant accumulation of immature B-cell precursors in bone marrow and other lymphoid organs. Although several intrinsic regulatory signals participating in BCP-ALL have been clarified, detailed intrinsic and extrinsic mechanisms that regulate BCP-ALL progression have not been fully understood. In the current study, we report that miR-582 is downregulated in BCP-ALL cells compared with normal B cells. Forced overexpression of miR-582 attenuated BCP-ALL cell proliferation and survival. We found that miR-582 overexpression disturbed the mitochondrial metabolism of BCP-ALL cells, leading to less ATP but more ROS production. Mechanistically, we identified PPTC7 as a direct target of miR-582. MiR-582 overexpression inhibited the activity of CoQ10, which is downstream of PPTC7 and played an important positive regulatory role in mitochondrial electron transportation. Finally, we found that overexpression of miR-582 upregulated the expression of immune checkpoint molecule CD276 and reduced NK cell-mediated cytotoxicity against BCP-ALL cells. CD276 blockade significantly increased NK cell-mediated cytotoxicity against miR-582-overexpressing BCP-ALL cells. Together, our research demonstrates that miR-582 acts as a negative regulator of BCP-ALL cells by reducing proliferation and survival, but protects BCP-ALL cells from NK cell-mediated cytotoxicity, suggesting that miR-582 may be a new therapeutic biomarker for BCP-ALL with CD276 blocker.